2021
DOI: 10.1111/ipd.12798
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Arabic short‐form version of the Family Impact Scale (FIS‐8)

Abstract: Considerable research attention has been devoted to developing and using condition-specific instruments to evaluate Health-Related Quality of Life (HRQoL) in clinical research. 1 Such measures are important in providing information on the impact of conditions and the extent and nature of treatment needs, in order to inform clinical decisions and assist in evaluating interventions and services. 2 A number of instruments have been developed to assess children's Oral Health-Related Quality of Life (OHRQoL). The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Currently, FIS is the only instrument available to assess the impact of the oral health status of children on the quality of life of the family. To date, its' validity and reliability have been demonstrated in various English-speaking countries [13,14], and non-English speaking ones, including Brazil [15,16], Libya [17], India [18,19], Finland [20], and Peru [12]. Despite an acceptable global internal consistency observed for FIS, the sub-scales presented questionable or unacceptable values.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, FIS is the only instrument available to assess the impact of the oral health status of children on the quality of life of the family. To date, its' validity and reliability have been demonstrated in various English-speaking countries [13,14], and non-English speaking ones, including Brazil [15,16], Libya [17], India [18,19], Finland [20], and Peru [12]. Despite an acceptable global internal consistency observed for FIS, the sub-scales presented questionable or unacceptable values.…”
Section: Discussionmentioning
confidence: 99%
“…The FIS-8 has had its validity demonstrated in other populations and cultures, such as Oman [ 6 ], New Zealand [ 3 ], Libya [ 16 ], England [ 17 ] and Saudi Arabia [ 18 ]. Those studies have all confirmed the scale’s validity, with marked gradients observed in mean scale scores across the ordinal categories of the global “gold standard” item(s) used.…”
Section: Discussionmentioning
confidence: 99%
“…a P < 0.001; df = 2; Chi-square = 54.35 b P < 0.001; df = 3; Chi-square = 184.15 c P < 0.001; df = 2; Chi-square = 214 16. …”
mentioning
confidence: 99%